Analysis and Optimization of the Influencing Factor on the Transmission Efficiency of MPV Car Driving Axle - Mo Yimin; Xie Xiongliang; He Ning; Wei Yong; Liang Junyong (Jixie chuandong)
The influence factors on the transmission efficiency of MPV car driving axle are analyzed by using the vehicle rear axle transmission efficiency test bench. After the experiment of the drive axle,it is found that the bearing is an important factor affecting the efficiency of the drive axle. The friction torque of bearing,bearing clearance and friction torque of the sealing ring are analyzed to find the main factor of friction torque.The results show that friction torque of the sealing ring,which is accounted for over 85%,is the main power consumer of the frication torque of rear axle. Moreover,the transmission efficiency of rear axle can be improved when bearing clearance increases in an appropriate way.